2012
DOI: 10.1093/eurpub/cks143
|View full text |Cite
|
Sign up to set email alerts
|

Impact of economic crisis and other demographic and socio-economic factors on self-rated health in Greece

Abstract: Our findings confirm the association of self-rated health with economic crisis and certain demographic and socio-economic factors. Given that the economic recession in Greece deepens, immediate and effective actions targeting health inequalities and improvements in health status are deemed necessary.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
117
4
15

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 166 publications
(147 citation statements)
references
References 26 publications
3
117
4
15
Order By: Relevance
“…The finding that self-rated health deteriorated between 2012 and 2013 is supported by published literature on the negative effect of crises on health [5,13]. It is interesting that this deterioration was found unanimously for all chronic patient groups under study.…”
Section: Discussionsupporting
confidence: 68%
See 2 more Smart Citations
“…The finding that self-rated health deteriorated between 2012 and 2013 is supported by published literature on the negative effect of crises on health [5,13]. It is interesting that this deterioration was found unanimously for all chronic patient groups under study.…”
Section: Discussionsupporting
confidence: 68%
“…Still, it included a number of questions based on a previously used questionnaire in a national survey [5]. The previous 6-months period for assessing health care utilization was chosen in order to minimize recall bias.…”
Section: Study Limitations and Study Strengthsmentioning
confidence: 99%
See 1 more Smart Citation
“…Early reports from Greece have demonstrated a negative effect of the financial crisis on respiratory health, resulting in increases in poor self-rated health [60], all-cause mortality [1, 5, 10, 61], outbreaks of infectious diseases [1,12], restrictions in access to healthcare [1,11,12,60,62] and mortality due to adverse events during medical treatment [61]. In terms of the number of years of life lost due to premature death in Greece, international reports found that from 2010 to 2015 COPD rose from the seventh to the fifth leading cause of premature death.…”
Section: Respiratory Mortality In Greece Amid An Economic Crisismentioning
confidence: 99%
“…1 Recession affects health by worsening health-related quality of life; [2][3][4] increasing the incidence of some communicable diseases; 5 and exacerbating mental ill health 2,5-9 and increasing suicide rates. 5,6 This impact is not direct, and can be buffered by the degree of social protection that the state offers.…”
Section: Introductionmentioning
confidence: 99%